ANALISIS PERENCANAAN PAJAK (TAX PLANNING) DALAM MENGEFISIENKAN PEMBAYARAN PAJAK TERUTANG PADA CV. MITRA BAHAGIA KENDARI - Oditama, Afkhasia (JURNAL AKUNTANSI, 2016)
This study aimed to analyze the costs previously not recognized as expenses by tax regulations to become recognizable expenses. This research uses a descriptive analysis which obtained through secondary data. The data used is qualitative data in the form of accounting policies and the quantitative data in the form of financial statements, as well as a list of fixed assets and accumulated depreciation in 2014.Results of this studyindicate that tax planning that can be done by CV. Mitra Bahagia Kendari, related to costs previously not recognized by tax regulations are to replace the provision of meal/drink expenses for employee into providing meal/drink for employees in the office, incorporate medical expenses in addition to the income of the employees, make a nominative list related to the cost of entertainment, and replace the method of depreciation of non-buildingfixed assets. The implementation of tax planning will allow CV. Mitra Bahagia Kendari to reduce the income tax burdento approximately 8.9% of the income tax before tax planning.Â Keywords: Tax Planning, Reducing Tax Burden, Corporate Income Tax.